“Beg, Borrow, and Steal”: School Division Perspectives of Assessment Policy Creation in Saskatchewan - Hebert, Cristyne; LeNouail , Kent (Alberta Journal of Educational Research, 2023)
This study focused on school division needs pertaining to classroom-based assessment policies in Saskatchewan. Using a critical policy analysis framework, this project narrowed in on the creation of assessment policies within school divisions in the province through the lens of superintendents (n = 16). Applying Verhoest et al.’s (2004) organizational autonomy framework, school divisions were interpreted as having both a minimum level of financial autonomy and a higher (though ultimately ambiguous) level of policy autonomy. Interviews revealed a tension between policy creation at the school-division level and within the Ministry, highlighted the impact of higher policy autonomy and lower financial autonomy on policy development and implementation at the division level, and called attention to a desire from school divisions for provincial guidance. Keywords: Classroom-based assessment; policy; school divisions; Saskatchewan; Ministry of Education Cette étude a porté sur les besoins des divisions scolaires en matière de politiques d'évaluation en classe en Saskatchewan. À l'aide d'un cadre d'analyse critique des politiques, ce projet s'est concentré sur la création de politiques d'évaluation au sein des divisions scolaires de la province dans l'optique des directions générales (n = 16). En appliquant le cadre d'autonomie organisationnelle de Verhoest et al. (2004),on a perçu les divisions scolaires comme ayant à la fois un niveau minimum d'autonomie financière et un niveau plus élevé (bien qu'en fin de compte ambigu) d'autonomie en matière de politiques. Les entrevues ont révélé une tension entre la création de politiques au niveau de la division scolaire et au sein du ministère, ont mis en évidence l'impact d'une autonomie politique plus élevée et d'une autonomie financière plus faible sur l'élaboration et la mise en œuvre de politiques au niveau de la division et ont attiré l'attention sur le désir des divisions scolaires d'obtenir une orientation de la part de la province. Mots clés : évaluation en classe ; politique ; divisions scolaires ; Saskatchewan ; ministère de l'Éducation